(untitled) (Hologramática, 2022)
Migratory flows are not a new phenomenon; however, it is increasingly common to observe attitudes of rejection on the part of the native population towards the arrival of immigrants because they perceive them as a threat, both from an economic and social point of view. Although numerous studies have shown that these concerns are unfounded because historically no adverse effects related to immigration have been verified, knowledge of the data does not change people’s opinions. This article examines why people need to believe that their opinions are valid and insist on them, even though there is evidence to the contrary. To do this, we begin by studying individual preferences in the framework of what economic theory holds, and then compare what is established by this theory with the results obtained in different experiments. We observe that the presence of stereotypes distorts respondents’ beliefs even after the actual facts are known. We conclude that the attitudes of rejection towards the immigrant population by the native population are the reflection of biased preferences.